Preliminary tests for mechanical properties of wooden 'buttons' used for attaching auxiliary supports behind panel paintings. (September 2015) - Mazzanti, Paola; Togni, Marco; Goli, Giacomo; Uzielli, Luca
<x content-type="archive" xml:space="preserve">Abstract</x> When wooden supports of panel paintings have been severely altered or damaged and the original cross beams are missing, new cross beams or other types of auxiliary supports are connected to the panel's back-face in order to achieve desired effects including panel strengthening and control of deformations. Some conservation laboratories use small wooden blocks, each glued on the back face of the panel and holding freely the head of a screw connected (often by means of springs) to the auxiliary support; such blocks being called in Italian 'piedini' or 'bottoni', the English term 'buttons' is proposed here. This paper reports research aiming to characterize the mechanical behavior of three types of 'buttons' having different geometries and made of various wood types (oak, walnut, lime, beech, and a medium density fiberboard). Short-term mechanical tests (∼1 minute duration) were performed with a universal testing machine by axially pulling out the 4 mm diameter steel screw from the button, glued onto a dummy board. Load and deformation were recorded, and the load–deformation curves were analyzed. The results show that the deformability and the load-carrying capacity of the buttons were influenced primarily by the manufacturing geometry and secondarily by the wood density.